Weight loss in a patient with polycystic kidney disease: when liver cysts are no longer innocent bystanders. Issue 5 (3rd September 2015) - Cecere, N.; Hakem, S.; Demoulin, N.; Hubert, C.; Jabbour, N.; Goffette, P.; Pirson, Y.; Morelle, J.
Abstract : Objective and importance: Autosomal dominant polycystic kidney disease (ADPKD) is the most frequent inherited kidney disorder, and liver involvement represents one of its major extra-renal manifestations. Although asymptomatic in most patients, polycystic liver disease (PLD) can lead to organ compression, severe disability and even become life-threatening, thereby warranting early recognition and appropriate management. Clinical presentation: We report the case of a 56-year-old woman with ADPKD and severe weight loss secondary to a giant hepatic cyst compressing the pylorus. Partial hepatectomy was required after failure of cyst aspiration and sclerotherapy, and patient's condition improved rapidly. Discussion and conclusions: We discuss the presentation and classification of compressing liver cysts, and the available therapeutic alternatives for this potentially severe complication of ADPKD.